Application of Random Amplified Polymorphic DNA Markers for Genetic Diversity Assessment of Pomegranate (Punica granatum L.) Cultivars in Duhok Governorate – Kurdistan of Iraq - Sinjare, Dalal Y.; Zubair, Sabrya J.; Ali, Avesta M.; Jubrael, Jaladet M.S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Random amplified polymorphic DNA (RAPD) markers were used to investigate the genetic diversity among 13 cultivars of pomegranate cultivated in Duhok governorate, Kurdistan region/Iraq. Unweighed pairgroup method average clustering divided the 13 cultivars into three main groups. In RAPD analysis, 12 out of 30 employed random primers showed good amplification and polymorphism on pomegranate samples with a total of 107 bands. The percentage of polymorphic DNA bands ranged from 66.6% (OPX-17) to 100% (OPO-07, OPS-17, and OPE-18, OPP-02, OPK-08, OPL-17, and OPR-01) with an average of polymorphic rate of 94.39. According to matrix coefficient, the lowest genetic similarity was observed between Soormiz and Rash Dendikheer (0.1065). The Dereger and Kapepan populations were most similar ones with coefficient of 0.9374.